Instructional Strategies for TEFL Online Learning - Novpitri, Aas; Juliardi (Journal of Linguistica, 2024)
The impact of the COVID-19 outbreak has led to the closure of educational institutions around the world, prompting the exploration of instructional strategies for online teaching in higher education. This case study develops effective online teaching methods without compromising the quality of student learning. Ideas for online education in developing countries, including maintaining the voice of the instructor, practicing vocal functions, and sharing resources before class, are considered. These strategies support improved student learning, with suggestions for collaboration between the Higher Education Commission and the telecommunications industry to address internet issues. Factors such as student feedback, flexible teaching and grading policies, and support from teaching assistants, play an important role in improving distance learning. TEFL certification is becoming an important component in job applications for teaching English abroad, offering the ability to teach English as a foreign language in various countries.